FRI0094 Kidney Function and Effectiveness of Methotrexate Treatment in Rheumatoid Arthritis Patients. (9th June 2015) - Studenic, P.; Alasti, F.; Smolen, J.S.; Haslacher, H.; Aletaha, D.
Abstract : Background: Treatment options for rheumatoid arthritis (RA) patients are manifold, but methotrexate (MTX) and leflunomide categorized as DMARDs of first choice in treating rheumatoid arthritis patients. Methotrexate accumulates in patients with impaired kidney function and should therefore be used cautiously. At the same time, such accumulation may also lead to an increased effectiveness. Objectives: To investigate the effects of methotrexate dose and kidney function on effectiveness, using patients treated with leflunomide as the control group. Methods: We identified patients starting either MTX or leflunomide treatment, who had clinical and laboratory follow up for at least 6 month out of a longitudinal observational database. By using multivariable regression analyses, we tested whether creatinine or glomerular filtration rate (GFR) besides baseline SDAI were associated with observed Simplified Disease Activity (SDAI) response. Results: 200 patients receiving MTX (74% female, Median (IQR): GFR=77 (67-90), SDAI=14 (7-23.1), 59% rheumatoid factor positive) and 46 receiving Leflunomide (89% female, Median (IQR): GFR=67 (61-81), SDAI=12 (6-18.6), 59% rheumatoid factor positive) were identified in our longitudinal observational database for analyses. Regression analyses in the MTX cohort showed that after adjusting for MTX dose higher creatinine was associated with higher SDAI response after 6 month of treatment (p=0.002). Analogously, in a separate analysis lower GFR was also significantly associated with larger clinical improvement (p=0.013) (Figure ). In patients treated with leflunomide creatinine as well as GFR was not associated with SDAI change after 6 month of treatment (p=0.254). Conclusions: Impaired kidney function is a risk factor for MTX accumulation and associated toxicity, at the same time, higher treatment responses in these patients indicate increased clinical benefit in these patients. This could also indicate room for higher doses in patients with normal kidney function, which is historically limited to 25mg/week. Disclosure of Interest: None declared